Associação de anti-helmínticos sintéticos e monoterpenos no controle de Haemonchus contortus - SILVA, Carolina Rocha e (2020)
Gastrointestinal nematodes from small ruminants resistant to synthetic anthelmintic products have been selected for several years. The use of monoterpenes, products present in essential oils of plants, can overcome this situation, helping to control Haemonchus contortus, through a synergistic effect with synthetic anthelmintics. However, to obtain an in vivo efficacy against ruminant nematodes, monoterpenes must reach target host sites where the nematodes are present without being degraded after their oral administration. The rumen fermentation process affects the components of food eaten by the host. Therefore, information about the metabolic fate of monoterpenes in the rumen is necessary before these compounds can be used in vivo. In addition, the combination of monoterpenes with synthetic anthelmintic products can be an interesting strategy to achieve interaction with the same target at different binding sites, and potential additive or synergistic effects between natural and synthetic products should be evaluated. By the way, the association with natural and synthetic products can act by altering the nematode's ultrastructure. The present work aimed to evaluate the ruminal stability, efficacy, and the effect on the ultrastructure and the biophysical characters of the association of synthetic compounds and monoterpenes on H. contortus. We conclude that the monoterpenes carvacrol and thymol are stable in rumen liquid. The association of synthetic products with monoterpenes significantly improves the efficiency of Albendazole and Levamisol on H. contortus in vitro, in addition to having chemical interactions and causing damage to the ultrastructure of H. contortus eggs.